Development of Learning Media Based On Positive Discipline to Improve the Character of Early Childhood - Jazriyah, Himmatul; Yuliantina, Irma (Kirana Publisher (KNPub), 2025)
Character building from an early age is an important foundation in shaping a child's personality in the future. Positive discipline is one approach that emphasizes character building without punishment or threats, but with positive reinforcement and fun learning. However, learning media that support the implementation of positive discipline in early childhood environments are still limited. Therefore, this study aims to develop a story book based on positive discipline, assess the feasibility of the book, and test its effectiveness in improving the character of early childhood. This research uses the research and development (R&D) method with the ADDIE model which consists of five stages: Analysis,Design,Development,Implementation, AndEvaluation. The subjects of the study were early childhood in two kindergarten institutions under the Al Furqon Islamic Foundation. Data were collected through interviews to analyze needs, questionnaires by three expert validations (materials, media and language) and observations. The material expert validator gave a total score of 77 with a percentage of 90.58%, the media expert validator gave an assessment score of 41 (percentage of 91.11%) and the language expert validator gave an assessment score of 37 (82.22%). The average percentage of validation by experts is 87.97%. From the percentage obtained, the story book based on positive discipline is in the very good qualification and is declared suitable for use. The level of effectiveness of positive discipline-based storybook products was measured through observations before and after using positive discipline-based storybook products. Before using the storybook, the average character score was 33.41. After being read the storybook, the average score was 41.8. From the results of data analysis using the test Wilcoxon Signed Rankshows that the p-value < 0.001. The p-value < 0.001 result means that there is a significant difference in the character of early childhood children before and after being read a story book based on positive discipline. Furthermore, to find out the extent of the difference in the results of character measurements before and after being read a story book, the value is calculatedeffect size rits value, which is 0.86. This showseffect sizer is high, meaning the difference between the scores before and after being read the story book is very significant.Therefore, from these results it is stated that the story books based on positive discipline produced are effective as a medium for improving the character of early childhood.